Principles of Wireless Sensor Networks - Obaidat, Mohammad S.; Misra, Sudip (Cambridge : Cambridge University Press, 2014)
Wireless sensor networks are an emerging technology with a wide range of applications in military and civilian domains. The book begins by detailing the basic principles and concepts of wireless sensor networks, including information gathering, energy management and the structure of sensory nodes. It proceeds to examine advanced topics, covering localisation, topology, security and evaluation of wireless sensor networks, highlighting international research being carried out in this area. Finally, it features numerous examples of applications of this technology to a range of domains, such as wireless, multimedia, underwater and underground wireless sensor networks. The concise but clear presentation of the important principles, techniques and applications of wireless sensor networks makes this guide an excellent introduction for anyone new to the subject, as well as an ideal reference for practitioners and researchers.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Wireless sensor networks